The Quest For Teaching Excellence - Alias, Abd Karim; Ahmad, Zainal Ariffin; See, Ching Mey (Centre for Development of Academic Excellence(CDAE), Universiti Sains Malaysia (USM), 2012)
The definition of teaching is the sharing or imparting of knowledge and skills either through formal or informal methods of instruction. Epistemology refers to the study of knowledge and how learning is acquired, and it addresses questions such as: What kind of learning do we want our students to have? What are the modes of delivery of knowledge? How do we ensure that our students are learning via best practices, such as Student- Centred Learning (SCL), Problem-Based Learning (PBL), and Contextual Learning?